Crystal structure of the catalytic domain of the Weissella oryzae botulinum‐like toxin. Issue 12 (31st May 2019) - Košenina, Sara; Masuyer, Geoffrey; Zhang, Sicai; Dong, Min; Stenmark, Pål
Abstract : Botulinum neurotoxins (BoNTs) are the most potent toxins known. So far, eight serotypes have been identified that all act as zinc‐dependent endopeptidases targeting SNARE proteins and inhibiting the release of neurotransmitters. Recently, the first botulinum toxin‐like protein was identified outside the Clostridial genus, designated BoNT/Wo in the genome of Weissella oryzae . Here, we report the 1.6 Å X‐ray crystal structure of the light chain of BoNT/Wo (LC/Wo). LC/Wo presents the core fold common to BoNTs but has an unusually wide, open and negatively charged catalytic pocket, with an additional Ca 2+ ion besides the zinc ion and a unique ß‐hairpin motif. The structural information will help establish the substrate profile of BoNT/Wo and help our understanding of how BoNT evolved. Abstract :